Peran Penting Pendidikan Agama Islam dalam Membentuk Karakter Pribadi yang Islami - Yusri, Nadia; Ananta, Muhammad Afif; Handayani, Widya; Haura, Nurul (Jurnal Pendidikan Islam, 2024)
Islamic Religious Education is considered one of the main pillars in shaping Islamic character among students. This education involves conscious efforts to convey, guide, and teach the values of Islam so that students can understand, internalize, and practice Islamic teachings in their daily lives. This article utilizes the library research method, drawing on various journal references and books that discuss Islamic Religious Education as a character builder. In this context, Islamic Religious Education is expected to play a significant role in shaping a society with strong moral responsibility and Islamic character. It is a long-term investment to create individuals who are not only intellectually intelligent but also possess noble character in accordance with Islamic teachings.